(untitled) - Williams, Dudley H. (London, 2008)
The book guides to the interpretation of the ultraviolet, infrated, nuclear magnetic resonance and mass spectra of organic compounds
Keywords: Chemistry, Organic,Spectrum analysis,Hóa học, hữu cơ,Phân tích quang phổ